Pengaruh Pendidikan Kesehatan terhadap Pengetahuan dan Tindakan Keluarga dalam Pencegahan Penularan Tuberkulosis - Vevi Suryenti Putri; Apriyali Apriyali; Armina Armina (Jurnal Akademika Baiturrahim Jambi, 2022)
Indonesia is a country with the third highest burden of tuberculosis (TB) in the world, after India and China. In 2018, an estimated 845,000 people fell ill and 93,000 died from tuberculosis. Based on 2017 data, 116,000 people died from tuberculosis and 98,000 people died in 2018. It is necessary to know and be aware that 75% of TB patients are in the productive group, meaning that they are in productive ages 15 to 55. The purpose of this study was to determine the effect of health education on family knowledge and actions in preventing tuberculosis transmission at the UPTD Puskesmas Payo Selincah Jambi City. This research is a quasi-experimental study with one group pre-post test. The study was carried out at the Payo Selincah Health Center UPTD, Jambi City and was carried out on January 15 to 22, 2022. The population in this study was 35 families with TB and the number of samples was 35 people with total sampling technique. Collecting data in this study using a questionnaire by filling out a questionnaire. Data analysis in this study is univariate and bivariate analysis using paired t-test. This study shows that there is a significant difference between the knowledge of respondents before and after being given health education as indicated by the p value of 0.000 and there is a significant difference between family actions on preventing tuberculosis transmission before and after being given health education with a p value of 0.000. From the research, it is hoped that health workers will carry out health education regarding the prevention of tuberculosis transmission and for further researchers.